NURSING CARE ACTIONS IN SERVING VICTIMS OF SCORPION STINGS IN PRIMARY HEALTH CARE - Edjane Xavier dos Santos Silva; Willames da Silva; Jorge Luiz Costa da Fonseca; Salmana Rianne Pereira Alves; Daiane Medeiros da Silva; Jordana de Almeida Nogueira; Débora Raquel Soares Guedes Trigueiro (Universidade Federal do Paraná, 2020)
Objective: To evaluate the knowledge and practices of nursing professionals in primary care. Method: An exploratory-descriptive study with a qualitative approach developed from February to March 2018 with 20 nurses from Family Health Units in Paraiba, Brazil, through semi-structured interviews, submitted to the thematic analysis technique. Results: It was verified that the nurses do not develop systematized care, but a punctual one, based on the signs and symptoms of the mild condition, and transfer the responsibility for handling the case to the reference service, due to lack of knowledge of the guideline established for the victim. In addition, 19 nurses do not carry out educational actions to prevent accidents and pass on the responsibility to the health surveillance system. Conclusion: The implementation of training programs, the elaboration of the Standard Operating Procedure, and the provision of health education for the professionals are necessary in order to improve the care provided to victims of scorpion bites.